Comparative Analysis of the Standards ANSI/IEEE C.37 and 141 and IEC 60909 for Short-Circuit Calculation in Industrial Systems - Muñoz Goez, John; Sosapanta Salas, Joseph Camilo; Noguera-Jiménez , Jhon (Ingeniería, 2026)
Context: Calculating short-circuit currents is key to equipment sizing and protection coordination in electrical power systems. However, methodological differences between ANSI/IEEE C.37 and 141 and IEC 60909 create uncertainty when selecting the most appropriate approach. This study addresses this problem through a comparative analysis based on computer simulations that evaluate both methodologies under equivalent conditions. Method: An industrial system with 44 busbars is modeled in ETAP (version 20.0), considering grid connection, local generation, and rotating loads. Short-circuit currents are calculated while following the procedures of both standards, and five representative fault points are analyzed. The evaluation includes six parameters: symmetrical inrush current, half-cycle closing current, peak fault current, interrupting current, asymmetrical breaking current, and steady-state current. Results: The IEC method yields values ​​between 5 and 10% higher than those obtained with ANSI/IEEE in most cases. The greatest differences are observed at busbars near generators and higher-power rotating machines, reaching up to 9.34% in the inrush current. These variations are mainly associated with the treatment of the X/R ratio and the voltage factor c applied in IEC. Conclusions: The IEC 60909 standard offers more conservative estimates for demanding designs, while ANSI/IEEE is useful in preliminary analyses, providing practical criteria for selecting the standard based on system criticality.